Comparison of different extraction methods for the extraction of total phenolic compounds from winter melon (Benincasa hispida) seeds - Bimakr, Mandana; Abdul Rahman, Russly; Taip, Farah Saleena; Mohd Adzahan, Noranizan; Sarker, Md. Zaidul Islam; Ganjloo, Ali (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Conventional Soxhlet extraction (CSE) and Ultrasound-assisted extraction (UAE) methods were applied for the extraction of total phenolic compounds (TPC) from winter melon (Benincasa hispida) seeds. Effects of different UAE variables such as amplitude (25-75%), temperature (45-65 °C) and sonication time (20-60 min) on the TPC of extracts was determined using complete randomised design (CRD). The results showed that the TPC of extracts obtained UAE process significantly affected by independent variables. The maximum value of TPC (22.12 ± 1.23 mg GAE/g extract) was obtained at the combined treatment conditions of 75%, 55 °C and 40 min. The UAE results obtained were compared with those achieved by using conventional Soxhlet extraction (CSE) method. It was found UAE allowed extraction at lower temperature and the extracts obtained posses higher quality compare with CSE. UAE is a promising environment friendly technique for the extraction of bioactive compounds from winter melon (Benincasa hispida) seeds.